79.2k views
4 votes
If f(x)=6x²-4 and g(x)=2x+2, find (f-g)(x)

User Holystream
by
4.5k points

2 Answers

3 votes

Answer:


(f-g)(x)=6x^(2)-2x-6

Explanation:

1) Given two functions f(x) and g(x) we can operate them like this:


f(x)+g(x)=(f+g)(x)\\f(x)-g(x)=(f-g)(x)\\f(x)*g(x)=(f*g)(x)\\f(x):g(x)=(f(x))/(g(x))

In this question the point is subtracting them, so:

2)


}\\\\f(x)=6x^(2)-4\, \:\:g(x)=2x+2\Rightarrow (f-g)(x)=6x^(2)-4-(2x+2)\Rightarrow (f-g)(x)=6x^(2)-4-2x-2\Rightarrow (f-g)(x)=6x^(2)-2x-6

This function has a Domain, as a polynomial function:


D=\left ( -\infty, +\right )

And an Range =


R=[(-37)/(6),\infty)

If f(x)=6x²-4 and g(x)=2x+2, find (f-g)(x)-example-1
User Akasha
by
4.8k points
5 votes

Answer:

6x² - 2x - 6

Explanation:

Note that (f - g)(x) = f(x) - g(x)

f(x) - g(x) = 6x² - 4 - (2x + 2) = 6x² - 4 - 2x - 2 = 6x² - 2x - 6

User Igor Loskutov
by
5.5k points